Predictive Analytics of the Likelihood Of Road Accidents by Location - Muhammed, Muhammad Bukhari (IRC, 2019)
This project is regarding the problem of the inability to relate the relationship between different factors in the event of road accident to the occurrence of road accident as well as the inability to forecast the occurrence of road accident. The solution that will be introduce by this project is a dashboard containing visuals of relationship between different factors to road accident. The dashboard will be created on a Microsoft software, PowerBi. The dashboard will also contain at least one visual that gives the statistic of the likelihood of future accident to happen by location which its algorithm will be coded in R programming and be embedded into the main dashboard. It will produce a very deep analytical results which will help contribute us in recognizing the likelihood of future accident locations and their factors so that the location can be improved to prevent the accidents.